Kinetic and thermodynamic studies of the formation of a polyurethane based on 1,6-hexamethylene diisocyanate and poly(carbonate-co-ester)diol - Fernández d’Arlas, Borja (2007)
This paper presents the kinetic and thermodynamic characterization of a non-catalyzed reaction between poly(hexamethylene carbonate-co-caprolactone)diol (PHMC-co-PCL) and aliphatic hexamethylene diisocyanate (HDI) with a stochiometric functional concentration, using both isothermal and dynamic differential scanning calorimetry, DSC, as well as Fourier transform infrared spectroscopy, FT-IR. DSC data were fitted using a Kamal autocatalytic equation. Model-free-isoconversional methods were also applied to analyse the conversion dependence of the global activation energy. This relation was used to predict the reaction conversion versus time pattern at different temperatures and to compare it with that of the model approach. Kinetic modelling and model-free analysis successfully described the conversion versus time curves. The reaction can be divided in two different paths: the forward path and the autocatalyzed one. Results corroborated that autocatalysis is promoted by the urethane group. Activation energies for both reaction paths have been found to be higher than those presented in the literature for aromatic diisocyanate systems, which explains the lower reaction rate of the presented system. © 2007 Elsevier B.V. All rights reserved.